2016
DOI: 10.1002/mus.24984
|View full text |Cite
|
Sign up to set email alerts
|

Reverse fiber type disproportion: A distinct metabolic myopathy

Abstract: Subjects with type II muscle fiber predominance exhibited exaggerated increases in ammonia and elevated CK levels during exercise. Predominance of type II fibers on muscle biopsy is the opposite finding of congenital fiber type disproportion; we suggest these patients be referred to as having "reverse fiber type disproportion." Muscle Nerve 54: 86-93, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Studies of lactate responses to maximum exercise in patients with myopathy show divergent results. Exaggerated lactate increases have been observed in a variety of muscle diseases, including inherited mitochondrial myopathy 20 and type II fiber predominance, 5 which may be due to inadequate ATP regeneration via oxidative metabolism in the muscle. 21 By contrast, 1 study showed reduced lactate levels at maximum exercise in individuals with mitochondrial myopathy.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Studies of lactate responses to maximum exercise in patients with myopathy show divergent results. Exaggerated lactate increases have been observed in a variety of muscle diseases, including inherited mitochondrial myopathy 20 and type II fiber predominance, 5 which may be due to inadequate ATP regeneration via oxidative metabolism in the muscle. 21 By contrast, 1 study showed reduced lactate levels at maximum exercise in individuals with mitochondrial myopathy.…”
Section: Figurementioning
confidence: 99%
“…These conditions have been associated with mild to moderately elevated serum CK levels, although no direct relationship to future myopathy development has been established . Other subjects from our database with elevated CK had biopsy‐diagnosed mitochondrial myopathy or type II fiber predominance . Still others had no notable symptoms apart from generalized myalgia and fatigue.…”
mentioning
confidence: 95%
See 1 more Smart Citation